Cachaça, por favor! Embates de representações na perspectiva do organizing. - Barbieri, Rafaela Costa Cruz (2019)
The present study aims to research “cachaça”, taking it as an object capable of elucidating the role of organizations in the construction of socio-cultural representations. In this way, the research is based on an "interdisciplinary" or even "transdisciplinary" reflection in which "cachaça" is problematized between two fields of academic knowledge Organizational Studies and Cultural History. In this sense, the organization is understood as a dynamic process of construction, organizing, and questions are posed about how and what representations are built about cachaça and what kind of interactions they establish among themselves. Academically, the research is justified for the importance of understanding the new contents that came to be associated with “cachaça” in Brazil, from the 1990s. New adjectives were conferred on the drink, such as gourmet, premium and artisanal, at the same time in that terms like regional and national have gained new clothes. Linked to these innovations, new audiences, new markets, investments of producing companies and new legislation, instigated the research to observe the performance of organizations related to the production of “cachaça”, in the troubled relationship of its subjects. The main argument of this thesis is that the clashes of representations are fought especially in the controversies currently placed on “cachaça”. Regarding the theoretical reference, the research adopts references a theoretical tool pertinent to Cultural History, representations; and dialogues directly with the references pertinent to Organizational Studies, when repositioning the representations in the perspective of organizing. Regarding the methodology, the research used written and imaging documents. The data collection was done in the production of folklorists, in the national legislation and the State of Minas Gerais; in various documents of state associations and federations; in notes from the SEBRAE to the productive sector. Television programs, advertising campaigns, labels, photographs, and narratives of subjects interviewed in the years of 2016 and 2017 were also analyzed. Finally, the research route that was proposed, going in search of the constituent elements of the representations of “cachaça”, has demonstrated that they do not always coexist harmoniously within organizing. On the contrary, there may be clashes between the organizations responsible for promoting those representations, expressing in them the disputes that occur between groups and subjects.